RANCANGAN INDEKS PERATURAN NAGARI DI KECAMATAN SUTERA KABUPATEN PESISIR SELATAN TAHUN 2010-2021 - Putri Bunda, Mega; Nurul Husna Zalmi, Fadhila; Rahmi, Lailatur; Hasfera, Dian (UIN Imam Bonjol Padang, 2022)
This research is motivated by the difficulty of the community in finding information on Nagari regulations because they are not widely disseminated. The purpose of this study was to design and produce an Index of Nagari Regulations in Sutera Subdistric, Pesisir Selatan Regency, 2010-2021 to facilitate users in tracing and obtaining information about valid, effective, and practical Nagari regulations. The method used in this research is the development method. The stages of the development method are need analysis, design stage, development stage, and product testing (evluation). The result of this study resulted in a product in the form of a Nagari Regulations Index book in Sutera District, Pesisir Selatan Regency, 2010-2021, which showed that the product had met the valid, practical, and effective criteria. This product is said to be valid, indicated by a value of A. This product is said to be practical based on the percentase of respondents, 90% strongly agrees and 10% agrees with large group trials. This product is said to be effective based on the assessment of the percentase of respondents 80% strongly agree and 20% agree with large group trials.